“Spreading the word” – Examining the dynamics of community engagement in HIV vaccine research at an HIV prevention research centre in the Western Cape South Africa - Lesch, Anthea M. (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2016.